Globalization-Challenges Faced by Women Entrepreneurs - Suriyamurthi, S.; Christina Sheela, S.; Uma Rani, T. S. (Prabandhan: Indian Journal of Management, 2009)
As technology speeds up lives and the new millennium is now upon us, it is useful to take time to reflect on what will surely be one of the driving forces of the global economy of the 21st century. Women are an emerging economic force that policymakers cannot afford to ignore. There are however a number of constraints to women owned businesses that need to be addressed. In overcoming these obstacles, there are actions to be taken by government, financial institutions and employers’ organizations by working closely with women business associations. It is important for women entrepreneurs to join hands with mainstream employers’ organisations so that these obstacles, challenges and problems can be turned into legitimate policies. Globally, women are enhancing, directing, and changing the face of how business is done today. Ultimately, female business owners must be recognized for who they are, what they do, and how significantly they impact the world’s global economy.